2022
DOI: 10.46792/fuoyejet.v7i2.799
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Impacts of Metal Recycling on Groundwater Quality in Ogijo, Ogun State, Nigeria

Abstract: Groundwater is an essential source of water supply globally. Recently, however, the groundwater environment is being threatened due to heavy metal contamination resulting from the indiscriminate use, storage, and disposal of toxic metal elements. This study evaluates heavy metals concentrations in groundwater systems close to a metal recycling industry in Ogun State, Nigeria. In the study, thirty-six (36) water samples were collected from boreholes within the vicinity of a metal recycling industry and analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…The concentration of Ca in this study was lower than that recorded in surface and pond water bodies around e-waste dump sites of Guzape, Karmo, and Kubuwa areas of Abuja, where the authors recorded Ca concentrations of 30.7, 35.4, and 24.8 mg/L respectively (Mukate et al, 2019). The concentration of Na in water samples contaminated by anthropogenic activities in rural east-central Illinois ranged from 0.8 to 12 mg/L, which was higher than what was reported in the present study (Balogun-Adeleye et al, 2022). Panno et al (2006) reported Pb concentrations in groundwater exceeding the WHO permissible limits for drinking water, with Pb concentrations ranging from 0.001 to 5.458 mg/L, which is higher than the Pb concentrations reported in the present study.…”
Section: Heavy Metal Concentration In Groundwater Samples Analyzedcontrasting
confidence: 78%
“…The concentration of Ca in this study was lower than that recorded in surface and pond water bodies around e-waste dump sites of Guzape, Karmo, and Kubuwa areas of Abuja, where the authors recorded Ca concentrations of 30.7, 35.4, and 24.8 mg/L respectively (Mukate et al, 2019). The concentration of Na in water samples contaminated by anthropogenic activities in rural east-central Illinois ranged from 0.8 to 12 mg/L, which was higher than what was reported in the present study (Balogun-Adeleye et al, 2022). Panno et al (2006) reported Pb concentrations in groundwater exceeding the WHO permissible limits for drinking water, with Pb concentrations ranging from 0.001 to 5.458 mg/L, which is higher than the Pb concentrations reported in the present study.…”
Section: Heavy Metal Concentration In Groundwater Samples Analyzedcontrasting
confidence: 78%
“…The most significant natural water resource on the planet is groundwater. In times of drought and when surface water sources are limited and precipitation patterns are uncertain, groundwater has shown to be an important source of water supply for a range of uses, including household, industrial, and irrigation (Saha and Ray, 2019;Rahmot et al, 2022). Around a third of people worldwide consider groundwater their main water source for various uses (FAO, 2017;Tsor et al, 2022).…”
Section: Introductionmentioning
confidence: 99%